Глава 3.11. Шлюбний договір як регулятор сімейних правовідносин подружжя: матеріальний та процесуальний аспект - Дякович, Мирослава Михайлівна (Цивільний та виконавчий процес: міжгалузеві зв’язки. Особливості розгляду судами певних категорій справ та виконання судових рішень. Монографія, 2024)
The author explores the significance of the marriage contract in the civil law context in this chapter and delves into the historical aspects of its development. The value of the marriage contract lies in the fact that through this agreement, a couple can alter the legal regime of joint ownership stipulated by law to a contractual regime, specifically, the regime of separate (personal private) ownership or partial ownership. The marriage contract serves as an effective means to protect oneself and one’s interests both during marriage and in case of its dissolution. The author analyzes and provides a comprehensive answer to the question of who can enter into a marriage contract based on status, age, and citizenship, including whether a representative of one of the parties can enter into a marriage contract through power of attorney.The conditions stipulated by the parties in the marriage contract are substantiated. The parties cannot, at their discretion, regulate their relations in the marriage contract only in cases where there is a direct prohibition established by the civil legislation: the prohibition arises from the content of the legislative act; such an agreement contradicts the essence of the relations between the parties. According to Part 4 of Article 93 of the Family Code of Ukraine, a marriage contract cannot place one of the spouses in an «extraordinarily disadvantageous financial position.»The work presents court cases that reinforce the discussed issues. The author examines the procedure for concluding a marriage contract, its content, and execution in this chapter. The emphasis is placed in this aspect on the issuance of an executive endorsement on the marriage contract in case the rights of one spouse to receive alimony from the other, as defined by this contract, are violated. Amendments to the marriage contract, refusal of the marriage contract, its dissolution, and recognition of its invalidity are legislatively defined by Articles 100, 101, 102 and 103 of the Family Code of Ukraine.A marriage contract may be declared void by a court decision at the request of one of the spouses or another person whose rights and interests are violated by this contract. The invalidity of the marriage contract entails certain legal consequences, as defined by the Civil Code of Ukraine, namely: 1) each party is obliged to return to the other party in-kind everything received for the execution of this legal transaction, and in case of impossibility of such return, compensate for the value of what has been received at prices prevailing at the time of compensation; 2) if, due to the commission of an invalid legal transaction, losses and moral harm are caused to the other party or a third party, they are subject to compensation by the party at fault. The recognition of the marriage contract as void does not affect the marriage. However, the recognition of the marriage contract as void entails the invalidity of the marriage contract. Among the consequences of declaring the marriage contract void is the restoration of the legal property regime.